Awareness, Practice and Level of Anxiety using Coronavirus Anxiety Scale among the Indian Population regarding COVID -19 Pandemic - Agarwal, Tanya; Bajpai, Prashant Kumar; Jaiswal, Kirti; Kumar, Sandip; Verma, Shreya; Shukla, Sushil Kumar (Indian Journal of Community Health, 2022)
Abstract: The most important aspect of Public Health Emergency Preparedness (PHEP) involves the circulation of trustworthy and accurate information in the public health interest domain. Strict stringency measures such as nationwide lockdown impacted people's mental health. Hence, this study was planned to assess the knowledge, practice, and anxiety among the Indian population about the ongoing pandemic in the initial phase. Methods: A web-based cross-sectional study was conducted between August 1, 2020, to October 5, 2020. Coronavirus Anxiety Scale was used to determine dysfunctional anxiety. Results: Among 553 participants, 73.6% had overall good knowledge of COVID-19 with mean correct score of 6.9±1.1. Majority of participants (97%) wore mask regularly, and 93% of respondents regularly washed their hands with soap and water. Only 14 participants scored ?9 on CAS, suggesting probable cases of dysfunctional anxiety associated with the COVID-19 crisis. Conclusion: The knowledge and practices of citizens in a nation reflect their preparedness and ability to deal with a pandemic of such proportion. Good knowledge translates to good practices and therefore reduces anxiety among the population. It is deemed necessary that people's knowledge and habits, including the mental impact, be accessed at periodic intervals to track their adaptation to pandemics over time.